Bioactive Properties of the Aqueous Extracts of Endophytic Fungi Associated with Scots Pine (Pinus sylvestris) Roots - Tienaho, Jenni; Karonen, Maarit; Muilu-Mäkelä, Riina; Kaseva, Janne; de Pedro, Nuria; Vicente, Francisca; Genilloud, Olga; Aapola, Ulla; Uusitalo, Hannu; Vuolteenaho, Katriina; Franzén, Robert; Wähälä, Kristiina; Karp, Matti; Santala, Ville; Sarjala, Tytti (Planta Medica, 2020)
Despite the continuing interest in various plant and natural products, only a small portion of the biologically active compounds from nature has been discovered and exploited. In this study, antioxidant and antibacterial properties of aqueous fractions of three endophytic fungi isolated from the roots of 8-year-old Scots pines (Pinus sylvestris) growing on a drained peatland were investigated. The endophytic fungi species were Acephala applanata, Phialocephala fortinii, and Humicolopsis cephalosporioides/Coniochaeta mutabilis. The bioactivities were examined using hydrogen peroxide scavenging and oxygen radical absorbance capacity tests as well as sensitive Escherichia coli-based biosensors, which produce a luminescent signal in the presence of substances with oxidative or genotoxic properties. In addition, cell models for Parkinsonʼs disease, age-related macular degeneration, and osteoarthritis were used to evaluate the potential for pharmaceutical applications. The aqueous extracts of fungi and 19 out of 42 fractions were found to be active in one or more of the tests used. However, no activity was found in the age-related macular degeneration and osteoarthritis cell model tests. Additionally, bioactivity data was connected with metabolites putatively annotated, and out of 330 metabolites, 177 were interesting in view of the bioactivities investigated. A majority of these were peptides and all three fungal species shared a highly similar metabolome. We propose that Scots pine endophytic fungi are a rich source of interesting metabolites, and synergistic effects may cause the bioactivities, as they were found to vary after the fractionation process.
Keywords: Acephala applanate; antibacterial; antioxidant; Coniochaeta mutabilis; endophytic fungi; Humicolopsis cephalosporioides; Leotimycetidae; Phialocephala fortinii; Sordariomycetidae